Investigation of the psychological factors associated with fissured tongue - Heron Fernando de Sousa GONZAGA; Lucinei Roberto de OLIVEIRA; Bruna Lavinas Sayed PICCIANI; Maria Lúcia Jorge de Sousa GONZAGA; Sílvia Angélica JORGE; Maria Augusta JORGE; Jane TOMIMORI (Faculdade São Leopoldo Mandic, 2019)
Objective: This study aimed to investigate the correlation between FT and anxiety. Methods: The sample consisted of 95 participants categorized into two groups: a) G-FT, 48 patients with FT and b) CG, 47 healthy participants. All patients were submitted to complete oral and dermatological examinations. The anxiety levels were measured using the State-Trait Anxiety Inventory (STAI). A p-value of < 0.05 was considered significant. Results: Fourteen (30%) patients reported awareness of having FT and 9 (64%) were women. Symptoms like burning feeling were reported by 3 (6%) only patients, all of then women. None of the control group patients presented these symptoms. In both groups, control and FT, the average scores of trait-anxiety were slightly higher than state-anxiety. There were no statistically significant differences between the FT and the control group related to the state-anxiety (p=0.724) and the trait-anxiety (p=0.680) scores. Study limitations: This study was limited by the number of subjects. Conclusion: Although moderate state-anxiety and trait-anxiety scores were determined, anxiety, as an environmental factor may not play a significant role in the development of FT. Considering FT as a multifactorial disease, probably a genetic component is necessary for expression.